Transmembrane Recognition of the Semaphorin Co-Receptors Neuropilin 1 and Plexin A1: Coarse-Grained Simulations - Aci-Sèche, Samia (Public Library of Science, 2014)
The cancer associated class 3 semaphorins require direct binding to neuropilins and association to plexins to trigger cell signaling. Here, we address the role of the transmembrane domains of neuropilin 1 and plexin A1 for the dimerization of the two receptors by characterizing the assembly in lipid bilayers using coarse-grained molecular dynamics simulations. From experimental evidence using a two-hybrid system showing the biochemical association of the two receptors transmembrane domains, we performed molecular simulations in DOPC and POPC demonstrating spontaneously assembly to form homodimers and heterodimers with a very high propensity for right-handed packing of the helices. Inversely, left-handed packing was observed with a very low propensity. This mode of packing was observed uniquely when the plexin A1 transmembrane domain was involved in association. Potential of mean force calculations were used to predict a hierarchy of self-association for the monomers: the two neuropilin 1 transmembrane domains strongly associated, neuropilin 1 and plexin A1 transmembrane domains associated less and the two plexin A1 transmembrane domains weakly but significantly associated. We demonstrated that homodimerization and heterodimerization are driven by GxxxG motifs, and that the sequence context modulates the packing mode of the plexin A1 transmembrane domains. This work presents major advances towards our understanding of membrane signaling platforms assembly through membrane domains and provides exquisite information for the design of antagonist drugs defining a novel class of therapeutic agents.